2013
DOI: 10.1007/s11250-013-0444-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and therapeutic effects of a novel granulated formulation of Artemisia extract on broiler coccidiosis

Abstract: The results suggested that this new formulation is a promising herbal medicine that can be used as a prophylactic or therapeutic product to control avian coccidiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…showed that chickens treated with A. sieberi extract has reduced oocysts count per gram of feces as well as improved growth performance parameters such as feed intake and weight gain when compared with the effects observed with monensin treatment (Pirali Kheirabadi et al, 2014). Similar results were recorded when day old broilers infected with E. tenella were treated with granulated extract of A. sieberi obtained from petroleum ether (Kaboutari et al, 2014). In addition, A. annua contain compounds which help birds maintain commensal microflora and take up large amounts of nitrogen.…”
Section: Phyto-chemicals (Herbal Extracts and Medicinal Plants)supporting
confidence: 56%
“…showed that chickens treated with A. sieberi extract has reduced oocysts count per gram of feces as well as improved growth performance parameters such as feed intake and weight gain when compared with the effects observed with monensin treatment (Pirali Kheirabadi et al, 2014). Similar results were recorded when day old broilers infected with E. tenella were treated with granulated extract of A. sieberi obtained from petroleum ether (Kaboutari et al, 2014). In addition, A. annua contain compounds which help birds maintain commensal microflora and take up large amounts of nitrogen.…”
Section: Phyto-chemicals (Herbal Extracts and Medicinal Plants)supporting
confidence: 56%
“… Eimeria tenella, Eimeria maxima, and Eimeria acervulina Improves feed conversion ratio and body weight gain. ( Del Cacho et al, 2010 ; Drăgan et al, 2010 , 2014 ; de Almeida et al, 2014 ; Kaboutari et al, 2014 ; Jiao et al, 2018 ) Leaf powder of A. annua Protects chickens from pathological symptoms and mortality associated with Eimeria tenella infection and reduces the lesion score, and fecal oocyst output. The leaf powder was more efficient than the essential oil, which could be due to a lack of artemisinin in the oil, and to the greater antioxidant ability of A. annua leaves than the oils.…”
Section: Phytochemical (Herbal) Remedies For Avian Coccidiosismentioning
confidence: 99%
“…One-day old broilers challenged by E. tenella on day 21 and treated with this extract showed a significant reduction in mortality, diarrhea, lesion scores, and oocyst number in feces. The authors suggest that this new formulation is a promising herbal medicine that can be used as a prophylactic or therapeutic product to control avian coccidiosis [ 67 ].…”
Section: Natural Alternatives To Controlling Coccidiosismentioning
confidence: 99%